ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN PELUMAS (STUDI KASUS PADA PT. FAJAR INDAH KUSUMA) - Suleman, Andini Tirta Cricela; Tinangon, Jantje J.; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Accounting Information System is an important thing owned by a company because the purpose and accounting information system is to provide information for users of accounting information that investors and other users inventory is one important component for a good company small and medium enterprises, and large companies. Because seen from the existing theory of inventory accounting information systems can provide many benefits for companies, especially PT. Fajar Indah Kusuma. The purpose of this study is to analyze whether the accounting information system inventory at PT. Fajar Indah Kusuma is adequate in the hope to provide benefits for the company, researchers and other parties. The method used in this research is the type of qualitative research that presents in the form of descriptive. While the data collection technique is done by direct survey to PT. Fajar Indah Kusuma and conducting interviews from several resource persons in the company. From the results of the study can be concluded that PT. Fajar Indah Kusuma not have adequate accounting information systems inventory where there are still short comings in the separator function dan internal control. The authors suggest that companies make impovements and evaluations on the system of divison of function and internal controls in order to run according to the system and efficient.Keywords : Analysis, accounting information systems, inventory